Biodegradation of 2-chloro-4-nitrophenol via a hydroxyquinol pathway by a Gram-negative bacterium, Cupriavidus sp. strain CNP-8 - Jun Min; Jinpei Wang; Weiwei Chen; Xiaoke Hu (AMB Express, 2018)
Abstract Cupriavidus sp. strain CNP-8 isolated from a pesticide-contaminated soil was able to utilize 2-chloro-4-nitrophenol (2C4NP) as a sole source of carbon, nitrogen and energy, together with the release of nitrite and chloride ions. It could degrade 2C4NP at temperatures from 20 to 40 °C and at pH values from 5 to 10, and degrade 2C4NP as high as 1.6 mM. Kinetics assay showed that biodegradation of 2C4NP followed Haldane substrate inhibition model, with the maximum specific growth rate (μ max) of 0.148/h, half saturation constant (K s) of 0.022 mM and substrate inhibition constant (K i) of 0.72 mM. Strain CNP-8 was proposed to degrade 2C4NP with hydroxyquinol (1,2,4-benzenetriol, BT) as the ring-cleavage substrate. The 2C4NP catabolic pathway in strain CNP-8 is significant from those reported in other Gram-negative 2C4NP utilizers. Enzymatic assay indicated that the monooxygenase initiating 2C4NP catabolism had different substrates specificity compared with previously reported 2C4NP monooxygenations. Capillary assays showed that strain CNP-8 exhibited metabolism-dependent chemotactic response toward 2C4NP at the optimum concentration of 0.5 mM with a maximum chemotaxis index of 37.5. Furthermore, microcosm studies demonstrated that strain CNP-8, especially the pre-induced cells, could remove 2C4NP rapidly from the 2C4NP-contaminated soil. Considering its adaptability to pH and temperature fluctuations and great degradation efficiency against 2C4NP, strain CNP-8 could be a promising candidate for the bioremediation of 2C4NP-contaminated sites.